Production of seed potatoes in Cyprus: incidence and economic importance of virus diseases - Vakis, N.J.; Ioannou, Nicolas (My University, 1988)
Since 1981 seed potatoes have been produced on a semi-commercial scale in Cyprus by single multiplication of imported class A stocks. The main virus in these locally produced seed potatoes was potato leaf roll virus (PLRV) which was detected in 369 of 658 seed crops examined, at an average incidence of ca 1.5% (range 0.1%-15%). Tuber infections were detected in 203 of 223 samples tested, at an average incidence of ca 6.8% (range 1-32%), indicating a considerable spread of the virus during local seed multiplication. Potato viruses Y, X and A, and alfalfa mosaic virus occurred at much lower incidence than PLRV. The effect of secondary PLRV infection on ware-potato yield was determined in the cultivars Spunta and Cara, each planted on two different dates. In all four cultivar-planting date combinations there was a very close negative correlation between yield and virus incidence. At 100% infection, losses in total yield varied from 46% (later planting of Cara) to 72% (earlier planting of Spunta). The threshold level of infection for significant losses was ca 10%.
Keywords: Cara; Planting date; Potato viruses; Spunta; Yield loss